2004
DOI: 10.1016/j.febslet.2004.12.013
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthetic routes for carbon monoxide and cyanide in the Ni–Fe active site of hydrogenases are different

Abstract: The incorporation of carbon into the carbon monoxide and cyanide ligands of [NiFe]-hydrogenases has been investigated by using 13 C labelling in infrared studies of the Allochromatium vinosum enzyme and by 14 C labelling experiments with overproduced Hyp proteins from Escherichia coli. The results suggest that the biosynthetic routes of the carbon monoxide and cyanide ligands in [NiFe]-hydrogenases are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
96
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 22 publications
(56 reference statements)
7
96
0
Order By: Relevance
“…Specific incorporation of 13 C from l-[ureido- 13 C]citrulline into the cyanide ligands to iron in Hyd-2 Citrulline can be used as a source of carbamoyl phosphate in vivo. To exclude carbamoyl phosphate synthesis from CO 2 , we used the strain DCar705AG/pBargI, a mutant devoid of carAB, argG and hycE (large subunit of Hyd-3) [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific incorporation of 13 C from l-[ureido- 13 C]citrulline into the cyanide ligands to iron in Hyd-2 Citrulline can be used as a source of carbamoyl phosphate in vivo. To exclude carbamoyl phosphate synthesis from CO 2 , we used the strain DCar705AG/pBargI, a mutant devoid of carAB, argG and hycE (large subunit of Hyd-3) [9].…”
Section: Resultsmentioning
confidence: 99%
“…In this study we show by in vivo labelling with L L-[ureido- 13 C]citrulline and 13 CO that in native, non-overproduced Hyd-2 from E. coli only the cyanide ligands are derived from carbamoyl phosphate and only the CO ligand is derived from the exogenously supplied carbon monoxide, as revealed by Fourier-transform infrared (FT-IR) spectroscopy. In the accompanying paper by Lenz et al the same labelling pattern is reported for the H 2 -sensing [NiFe]-hydrogenase from Ralstonia eutropha, the genes hoxBC and hypABCDE for which were heterologously overproduced in E. coli.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The two hyp gene products HypA and HypB together with the auxiliary protein SlyD [7][8][9] are required for nickel sequestration and incorporation, whereas the four other Hyp proteins (HypC to HypF) are involved in synthesis of the CN ligand and the cyanation of the active site iron [10][11][12][13]. The source and biosynthesis of the CO ligand are still unknown [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since amongst all the maturation proteins HypD is the only one with a redox-active cofactor [13,14] it may be involved in this electron transfer. As a first step in testing this assumption we have conducted a genetic screen for amino acid residues of HypD with functions in the maturation process.…”
Section: Introductionmentioning
confidence: 99%